Does Pyroptosis Play a Role in Inflammasome-Related Disorders? - Zhang, Jiajia; Wirtz, Stefan (International Journal of Molecular Sciences, 2022)
Inflammasomes are multiprotein complexes orchestrating intracellular recognition of endogenous and exogenous stimuli, cellular homeostasis, and cell death. Upon sensing of certain stimuli, inflammasomes typically activate inflammatory caspases that promote the production and release of the proinflammatory cytokines IL-1 beta, IL-1 alpha, and IL-18 and induce a type of inflammatory cell death known as "pyroptosis". Pyroptosis is an important form of regulated cell death executed by gasdermin proteins, which is largely different from apoptosis and necrosis. Recently, several signaling pathways driving pyroptotic cell death, including canonical and noncanonical inflammasome activation, as well as caspase-3-dependent pathways, have been reported. While much evidence exists that pyroptosis is involved in the development of several inflammatory diseases, its contribution to inflammasome-related disorders (IRDs) has not been fully clarified. This article reviews molecular mechanisms leading to pyroptosis, and attempts to provide evidence for its possible role in inflammasome-related disorders, including NLR pyrin domain containing 3 (NLRP3) inflammasome disease, NLR containing a caspase recruitment domain 4 (NLRC4) inflammasome disease, and pyrin inflammasome disease. Although the specific mechanism needs further investigations, these studies have uncovered the role of pyroptosis in inflammasome-related disorders and may open new avenues for future therapeutic interventions.
CRIS-Team WoS Importer:2022-09-30

Spatially resolved transcriptomics and graph-based deep learning improve accuracy of routine CNS tumor diagnostics - Ritter, Michael; Blume, Christina; Tang, Yiheng; Patel, Areeba; Patel, Bhuvic; Berghaus, Natalie; Kada Benotmane, Jasim; Kückelhaus, Jan; Yabo, Yahaya; Zhang, Jiajia; Grabis, Elena; Villa, Giulia; et al. (Nature Cancer, 2025)
The diagnostic landscape of brain tumors integrates comprehensive molecular markers alongside traditional histopathological evaluation. DNA methylation and next-generation sequencing (NGS) have become a cornerstone in central nervous system (CNS) tumor classification. A limiting requirement for NGS and methylation profiling is sufficient DNA quality and quantity, which restrict its feasibility. Here we demonstrate NePSTA (neuropathology spatial transcriptomic analysis) for comprehensive morphological and molecular neuropathological diagnostics from single 5-µm tissue sections. NePSTA uses spatial transcriptomics with graph neural networks for automated histological and molecular evaluations. Trained and evaluated across 130 participants with CNS malignancies and healthy donors across four medical centers, NePSTA predicts tissue histology and methylation-based subclasses with high accuracy. We demonstrate the ability to reconstruct immunohistochemistry and genotype profiling on tissue with minimal requirements, inadequate for conventional molecular diagnostics, demonstrating the potential to enhance tumor subtype identification with implications for fast and precise diagnostic workup.
CRIS-Team Scopus Importer:2025-02-14